Memory: A Very Short Introduction - Foster, Jonathan K. (New York Oxford University Press, 2009)
This Very Short Introduction brings together the latest research in neuroscience and psychology - weaving in case-studies, anecdotes, literature, and philosophy - to explore and explain the science of memory - how it works, and why we can't live without it
Includes Index and Illustrations.
Keywords: Memory